The potential contribution of selected forage legume pastures to cereal production in crop-livestock farming systems - Tarawali, Shirley A.; Peters, Michael (Cambridge University Press, 1996)
The potential of 3-year-old grazed pastures of Stylosanthes hamata, Chamaecrista rotundifolia and Centrosema pascuorum to contribute to subsequent maize production was investigated in subhumid Nigeria in 1993. All three legume pastures had the ability to give better maize grain yields than native pasture but this was significant only for Stylosanthes hamata and Chamaecrista rotundifolia. For the legume species, maximum yield of maize per kg of N applied was attained at 60 kgN/ha. The subsequent yield of maize could be related to the legume species used, pasture management and the length of the fallow period. Centrosema pascuorum behaved as an annual, and as such there was little legume present after 3 years; crop yield was therefore relatively low. Nevertheless, this species could be useful in 1-year fallow/pasture situations. Maize cropping was economically viable for legume plots only with 60 or 120 kgN/ha and not for native pasture. There was no significant differences in the time required to till or to weed legume pastures as compared with native pasture. Forage legume pastures could also have a positive effect on maize residue yields which represent a fodder resource in addition to the herbage understorey remaining after cropping, the quality of which could be enhanced by the presence of the forage legumes. The use of forage legumes for the promotion of both crop and livestock production in sustainable agricultural systems is discussed. The results of the study are used to highlight the importance of selecting the appropriate legume species, pasture management practices and duration of fallow period in relation to the prevailing farming system to maximize benefits from the legumes.